GENETIC DIVERSITY AND ASSOCIATION ANALYSIS FOR YIELD TRAITS CHICKPEA (CICER ARIETINUM L.) UNDER RICE BASED CROPPING SYSTEM - P. L. JOHNSON, R. N. SHARMA H. C. NANDA, (The Bioscan, 2015)
The experimental material comprised of 112 genotypes (85 Germpasm accession, 12 improved varieties and 15 advance breeding lines) of chickpea carried out to study the nature and magnitude of genetic divergence using Mahalanobis’s D2 statistics, correlation using Miller and path analysis by Dewey and Lu. 112 genotypes of chickpea were grouped in eight cluster. The highest inter cluster distance was observed clusters IV and VII (6.296) followed by I and VII (5.867), IV and V (5.681), I and IV (5.658). The highest intra-cluster distance was observed for cluster V (2.328). Hence, genotypes belonging to this cluster viz. ICC 251834, ICC 275466, ICC 269530, Indira Chana-1, ICC 269563, RG 2011-01, RG 2011-03, JG 11 can be utilized as parents in future chickpea improvement programmes. Correlation coefficient analysis revealed that biological yield and harvest index exhibited the positive correlation with seed yield per plant. path coefficients for seed yield per plant recorded the highest positive direct effect contributing to seed yield plant-1 is harvest index, biological yield and pods plant-1.